Justice for crime victims: has the time finally come for a radical paradigm shift? - Fattah Ezzat A. (Temida)
How is it that punishment has become synonymous with justice and that justice has become a euphemism for punishment? How is it that justice and punishment have become almost interchangeable terms? How is it that slogans such as ‘justice for victims’ are invariably interpreted as demands for more and harsher punishments. Is punishment truly synonymous with justice? Are crime victims really bloodthirsty and totally obsessed with a quest for punishment? A troubling question that has haunted me throughout my professional life, a question that I spent many sleepless nights trying to find the answer to, is: How could it be that punishment, the deliberate infliction of pain and suffering, the deprivation of liberty, or deliberately putting a human being full of life to death be called or perceived as justice and be seen as the most appropriate response to victims’ sufferings? How is it that victims who, as Nils Christie said, are the primary owners of the conflict (Christie, 1977) whose property rights were usurped, and whose rightful dues paid to them in the form of “Wergeld” or the composition was expropriated by the state, were led to believe that justice is vengeance and retaliation and that the harsher the punishment, the more just is the judgment? How is it that the theological and abstract notions of retribution, expiation, atonement and penitence became so entrenched in people’s minds that no rational thinking, no scientific evidence, no economic crisis, no humanitarian endeavour seems to be capable of shaking such religious beliefs or lessening the incessant demands for punishment? How is it that punishment has become so universally accepted, extremely popular and so widely practised that people and governments, even in the harshest economic times, are more than willing to waste billions and billions of dollars for no other reason but to inflict pain and suffering on those fellow citizens who have violated man-made laws? The time has come to ask whether 21st century society has undergone a social, cultural and moral evolution that makes the retributive ‘justice for victims’ paradigm ripe for a radical shift? These are just some of the complex and difficult questions that are begging for answers and that will be examined in this paper.